APOE-E4 and APOE-491A polymorphisms in individuals with subjective memory loss - Laws, S.; Clarnette, R; Groth, David (Nature Publishing Group, 2002)
The accurate clinical diagnosis of Alzheimer’s disease can only be made with a high degree of certainty in specialized centres. The identification of predictive or diagnostic genetic factors may improve accuracy of disease prediction or diagnosis. One major genetic risk factor, the ε4 allele of the apolipoprotein E gene, is universally recognised. We have recently shown that the A allele of the apolipoprotein E, −491A/T promoter polymorphism is also an important risk factor for Alzheimer’s disease in an Australian population. We designed the present study to investigate the association between apolipoprotein E genotype, −491A/T polymorphism, plasma apoE levels and the subjective experience of memory decline among 98 subjects and 49 age, gender and education-matched normal controls. An increased frequency of the ε4 allele of apolipoprotein E was significantly associated with the ‘memory complainers’ group (OR = 2.35, P = 0.02) as was the A allele of the −491A/T polymorphism (OR = 2, P = 0.02). Among all subjects, only seven individuals were homozygous for both of these alleles, and six of these seven individuals belonged to the ‘memory complainers’ group. This sub-group also had relatively elevated plasma apolipoprotein E levels (P0.01) and tended to score lower on the Mini-Mental State Examination (MMSE) and Cambridge Cognition Test. These data suggest that the ε4 allele of apolipoprotein E and the −491A allele are over-represented among individuals who complain of memory difficulties. Follow-up studies should clarify whether these genotypes and phenotypes are useful in the prediction and/or diagnosis of Alzheimer’s disease.